2023
DOI: 10.1007/s43032-023-01287-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetics in Preterm Birth

Abstract: Preterm birth (PTB), defined as the birth of a child before 37 completed weeks gestation, affects approximately 11% of live births and is the leading cause of death in children under 5 years. PTB is a complex disease with multiple risk factors including genetic variation. Much research has aimed to establish the biological mechanisms underlying PTB often through identification of genetic markers for PTB risk. The objective of this review is to present a comprehensive and updated summary of the published data r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 190 publications
0
3
0
Order By: Relevance
“…PTBs occur at less than 37 weeks' gestational age, accounting for 75% of perinatal mortality. Up to now, the preterm birth rate has risen dramatically in most industrialized countries; it is estimated to be around 12-13% in the USA and 5-9% in Europe [13,16]. Despite its high incidence, the exact pathogenesis of preterm delivery is still not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTBs occur at less than 37 weeks' gestational age, accounting for 75% of perinatal mortality. Up to now, the preterm birth rate has risen dramatically in most industrialized countries; it is estimated to be around 12-13% in the USA and 5-9% in Europe [13,16]. Despite its high incidence, the exact pathogenesis of preterm delivery is still not known.…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates report that PTB affects approximately 11% of all livebirths, or approximately 15 million PTB per year [12]. Twin studies have also suggested that genetics account for 17-36% of PTB risk [13]. In attempting to understand the heritability of PTB, both maternal and fetal genetics have been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation